Bias Filsafat Barat dalam Tafsir Modern Muhammad ‘Abduh - Fuad Syukri (Qur'an and Hadith Academic Society, 2014)
Contrary to the views of some scholars which state that Muhammad ‘Abduh’s rational interpretation of the Qur’an was influenced by Mu‘tazilah, this article reveals that some interpretations which have emerged in the 19th century, especially related to al-Kauniyah verses, have been influenced by the Positivism paradigm. In order to prove that, the writer discusses ‘Abduh’s Tafsir al-Qur’an al-Karim Juz’ ‘Amma and shows how his interpretation was based on the philosophy of Positivism.